2017
DOI: 10.4184/asj.2017.11.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Outcome of Transpedicular Decompression and Instrumented Fusion in Thoracic and Thoracolumbar Tuberculosis

Abstract: Study DesignRetrospective analysis.PurposeWe evaluated the functional, neurological, and radiological outcome in patients with thoracic and thoracolumbar tuberculosis operated through the transpedicular approach.Overview of LiteratureFor surgical treatment of thoracic and thoracolumbar tuberculosis, the anterior approach has been the most popular because it allows direct access to the infected tissue, thereby providing good decompression. However, anterior fixation is not strong, and graft failure and loss of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 22 publications
4
15
0
2
Order By: Relevance
“…The ODI score was reduced to 34 (10–74) at 6 months after posterior instrumentation. These results are consistent with research by Jain et al According to Jain et al there was a decrease in VAS score from 8.7 preoperatively to 2.1 at 6 months postoperatively [ 8 ]. Improvements in VAS scores at 6 months post posterior instrumentation could occur due to spinal nerve decompression along with improvement in kyphosis deformity.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The ODI score was reduced to 34 (10–74) at 6 months after posterior instrumentation. These results are consistent with research by Jain et al According to Jain et al there was a decrease in VAS score from 8.7 preoperatively to 2.1 at 6 months postoperatively [ 8 ]. Improvements in VAS scores at 6 months post posterior instrumentation could occur due to spinal nerve decompression along with improvement in kyphosis deformity.…”
Section: Discussionsupporting
confidence: 92%
“…Another study by Okada et al reported superior outcomes with more loss of correction, small and shorter duration of hospitalization in posterior instrumentation compared with surgical technique without instrumentation [ 6 ]. Other studies reported improvement of HRQOL and pain control after posterior instrumentation in spondylitis tuberculosis [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…have found the greater correction of kyphosis in lumbar and lumbosacral as compared to thoracolumbar studies. [29] This is attributed to more rigid thoracic vertebrae with rib attachments. Segmental spinal fixation, such as the pedicles screw system, allows for additional procedures such as closing wedge osteotomy, interbody fusion using bone graft with or without cages.…”
Section: Discussionmentioning
confidence: 99%
“…На фоне определенной стабилизации эпидемиологической ситуации по туберкулезу за рубежом и в Россий-ской Федерации в течение последнего десятилетия, в том числе касающейся заболеваемости туберкулезным спондилитом, составляющим 1,0-2,5 случая на 100 тыс. населения [5,11,17,29,33,46,62], отмечаются увеличение доли пациентов с множественными и распространенными формами заболевания [12, 14, 15, 26-28, 37, 59, 62] и двукратный рост числа заболеваний, вызванных лекарственно устойчивыми формами микобактерий туберкулеза [14,17]. Кроме того, число послеоперационных инфекционных осложнений, регистрируемых у таких больных, достигло 6-12 % [4,14].…”
Section: Discussionunclassified
“…Показаниями для хирургического лечения являются очаг костной деструкции, паравертебральные и эпидуральные абсцессы, деформации позвоночника с выраженным кифозом, неврологические дисфункции [16,45,56]. Длительное время абсцессотомия, передняя декомпрессия спинного мозга и передний спондилодез были золотым стандартом в хирургии инфекционных спондилитов [2,6,7,16,18,19,22,23,[32][33][34]49] [1,9]. К недостаткам переднебокового доступа к позвоночнику можно отнести риск повреждения магистральных сосудов, недостаточную возможность коррекции кифоза и некоторую (в пределах 5-10 %) потерю коррекции деформации в послеоперационном периоде [1,9,22].…”
Section: Discussionunclassified